2023
DOI: 10.1038/s41531-023-00508-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deep brain stimulation in Parkinson’s disease reflected in EEG microstates

Abstract: Mechanisms of deep brain stimulation (DBS) on cortical networks were explored mainly by fMRI. Advanced analysis of high-density EEG is a source of additional information and may provide clinically useful biomarkers. The presented study evaluates EEG microstates in Parkinson’s disease and the effect of DBS of the subthalamic nucleus (STN). The association between revealed spatiotemporal dynamics of brain networks and changes in oscillatory activity and clinical examination were assessed. Thirty-seven patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The analysis of EEG microstates is a popular technique for exploring scalp EEG data with a focus on the behavior of large-scale brain networks and brain dynamics (Khanna et al, 2015;Michel and Koenig, 2018). The spatiotemporal parameters of the main prototypical microstate maps are evaluated in healthy subjects (Bréchet et al, 2019;Jabès et al, 2021;Liu et al, 2020), and their alterations are explored in the context of psychiatric (Nishida et al, 2013;Sverak et al, 2021) and neurological diseases (Lamoš et al, 2023(Lamoš et al, , 2021. Some EEG/fMRI studies (Agrawal et al, 2022;Rajkumar et al, 2021;Schwab et al, 2015;Zappasodi et al, 2019) reported and assigned physiological significance to a topography with a distinct vertical line; we refer to this vertical topography as VT. Our study demonstrates that VT is partially a reflection of artifacts very likely caused by the movement of metallic parts of the EEG cap.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of EEG microstates is a popular technique for exploring scalp EEG data with a focus on the behavior of large-scale brain networks and brain dynamics (Khanna et al, 2015;Michel and Koenig, 2018). The spatiotemporal parameters of the main prototypical microstate maps are evaluated in healthy subjects (Bréchet et al, 2019;Jabès et al, 2021;Liu et al, 2020), and their alterations are explored in the context of psychiatric (Nishida et al, 2013;Sverak et al, 2021) and neurological diseases (Lamoš et al, 2023(Lamoš et al, , 2021. Some EEG/fMRI studies (Agrawal et al, 2022;Rajkumar et al, 2021;Schwab et al, 2015;Zappasodi et al, 2019) reported and assigned physiological significance to a topography with a distinct vertical line; we refer to this vertical topography as VT. Our study demonstrates that VT is partially a reflection of artifacts very likely caused by the movement of metallic parts of the EEG cap.…”
Section: Discussionmentioning
confidence: 99%
“…The generation, coding, transmission and integration of information in the brain are completed through the action potentials of neurons, because neuron is the smallest structure and functional unit of the nervous system 4 – 6 . The recording of individual neuron activity and local neuron population activity could help obtain the characteristics of action potentials, and also decode brain activity from multiple scales 7 9 , which is particularly important for exploring the mechanisms of DBS 10 , 11 .…”
Section: Background and Summarymentioning
confidence: 99%
“…These algorithms aim to provide a non-invasive and cost-effective means of diagnosing PD. Brain conditions like tumors, Parkinson's disease, and multiple sclerosis can be detected through various brain imaging methods, including structural magnetic resonance imaging (sMRI), functional magnetic resonance imaging (fMRI), positron emission tomography (PET), or electroencephalography (EEG) [2]. Various machine learning and image processing techniques are employed to identify brain disorders.…”
Section: Introductionmentioning
confidence: 99%